Compreensão e mobilização de conhecimentos por professores de geografia frente à mudança curricular - Iancey de Lacerda Teixeira (2024)
This study investigated the understanding and application of the Minas Gerais - Brazil Reference Curriculum (CRMG, in Portuguese) within the scope of the Geography curriculum component. The main objective is to analyze whether the recommendations of this curriculum are effectively understood and incorporated into the practice of Geography teachers. Knowledge of the curriculum is considered to be an essential pillar in a teacher's knowledge base and an enabler for the construction of powerful knowledge, since it is an instrument that directs the selection of content and cultures to be developed in the educational environment. Although the CRMG was built on the guidelines of a universal basis, the Common National Curriculum Base (BNCC, in Portuguese), we understand that there is no single curriculum that meets all realities. However, the articulation of the teacher's knowledge base, such as an understanding of the role of the curriculum and the construction of knowledge, creates conditions for the development of a more comprehensive curriculum. The subjects of the research were public school geography teachers who tutored undergraduates enrolled in the class Analysis of Pedagogical Practice in Geography - Internship II, offered at the Federal University of Minas Gerais. Once the teachers had signed up for the research, five semi-structured interviews were carried out during the second semester of 2023, seeking to understand aspects of initial training, continuing training and the appropriation of the CRMG indications in their practice. In Geography Teaching, we sought to identify how teachers understand skills, competencies, problem-solving, geographical reasoning and geographical situation, the latter being one of the concepts we believe to be crucial in transforming transmissive and descriptive teaching into a full possibility of exercising geographical reasoning and understanding spatiality. To analyze the interviews, we used the content analysis technique proposed by Laurence Bardin related to the theory of Michael Young, Clermont Gauthier and the theoretical references of Geography Teaching. Although we observed advances in Geography teaching with the incorporation of the BNCC guidelines into the structure of the Minas Gerais Reference Curriculum, we identified some weaknesses, such as the absence of clearer demonstrations of the geographical situation using a specific method, so that the skills still have a prescriptive tone. Geography teachers who took part in this research have a knowledge base that allows them to understand and mobilize the CRMG indications based on what it presents.